Complete atrioventricular block as a clinical manifestation of cardiac sarcoidosis - M. V. Serova; M. G. Poltavskaya; Yu. Yu. Garmash; D. A. Ivanova; E. S. Pershina; Yu. Zyuzya; Yu. S. Sazonova; M. Yu. Lukin; I. V. Samoilenko; M. A. Uyanaeva; A. L. Syrkin; G. G. Melkonyan (Российский кардиологический журнал, 2019)
Cardiac involvement in sarcoidosis is considered quite rare, but it can cause the first significant disease manifestations and patient’s death. Timely disease detection improves the effectiveness of treatment and prognosis. The article presents modern approaches to the diagnosis and management of patients with cardiac sarcoidosisusing clinical case of a patient hospitalized by ambulance with a first revealed symptomatic third-degree atrioventricular block. We described methods of examining this patient, as well as difficulties in differential diagnosis.